PENGELOLAAN PENDIDIKAN ANAK USIA DINI MELALUI PENDEKATAN SENTRA DAN SAAT LINGKARAN (BEYOND CENTERS AND CIRCLES TIME) DI PLAYGROUP AL KAUTSAR DESA KEBONAN KECAMATAN KARANGGEDE KABUPATEN BOYOLALI - Ikhsan, M. Yusuf Nur (2011)
This research purposes to describe character of (1) early children education planning through beyond centers and circles time (BCCT) approach in Al Kautsar play group Kebonan, Karanggede sub district Boyolali district. (2) early children education execution thoruh beyond centers and circles time (BCCT) aproach in Al Kautsar play group Kebonan, Karanggede sub district Boyolali district. (3) early children education result through beyond centers and circles time (BCCT) approach in Al Kautsar playgroup Kebonan, Karanggede sub district Boyolali district. Research location is in Al Kautsar Play group Kebonan, Karanggede sub district Boyolali district, this research is a qualitative research. Getting data in research uses documentation method (as main method), observation method, interview method. Data analysis technique in research uses descriptive technique with three procedures as: (1) data reduction, (2) data presentation, and (3) conclusion/ verification. Research results: (1) Al Kautsar play group program planning, design in curricular program and extra curricular program, the curricular program related to managed language improvement in lesson plan with basic competency and indicator, while planned extracurricular including: English activity, painting, dancing, computer, swimming and Iqro. (2) Beyond centers and circles time (BCCT) executes to stimulate student in doing playing with studying activity actively in learning centrals, to improve emotional social, cognitive improvement, and languange improvement. For improving language, teacher communicates effectively to children, with asking many problems to children so they have braveness to give their opinior to teacher, and their friends. (3) early children education result has been noted in curriculum, including 9 intelligences improvement ability such: linguistic intelligence, visual spatial intelligence, musical/ rhytmic intteligence, bodily/ kinesthetic intelligence, naturalist intelligence, interpersonal intelligence, spiritual intelligence, and intrapersonal intelligence.